Work Engagement in India: Validation of the Utrecht Work Engagement. (September 2013) - Kataria, Aakanksha; Garg, Pooja; Rastogi, Renu
This study aims at delineating the recent worldwide developments in the factorial structure of popular work engagement measure, the Utrecht Work Engagement Scale (UWES) and exploring its psychometric properties in terms of factorial validity, scale reliability, descriptive statistics and discriminant validity in an Indian sample of working population. The study is based on cross-sectional questionnaire survey responses from 304 Indian employees working in ITES. We conducted confirmatory factor analyses to compare the fit of a three-factor model to that of an alternative one-factor model of UWES-9 followed by an analysis of discriminant validity of UWES-9 in relation to organisational citizenship behaviour questionnaire (OCBQ) and organisational commitment questionnaire (OCQ) using chi-square difference tests. A comprehensive review of validation studies of UWES across other nations of the world in different time, culture and context represents instability of its factorial structure. Empirical evidences demonstrate a better fit of multidimensional structure of UWES-9 in comparison to that of unidimensional solution for the construct in the Indian context and support the discriminant validity of UWES-9 against OCQ and OCBQ. The study provides first direct evidence for the psychometric properties and unique identification of the UWES-9 in the Indian context.